Efficacy of group‐based multi‐component psycho‐education for caregivers of people with dementia: A randomized controlled study. Issue 7 (4th May 2021) - Seike, Aya; Sumigaki, Chieko; Takeuchi, Sayaka; Hagihara, Junko; Takeda, Akinori; Becker, Carl; Toba, Kenji; Sakurai, Takashi
Abstract : Aim: The aim of this study was to examine the ability of a group‐based multi‐component psycho‐educational intervention (GMC‐PEI) to reduce depression, and improve caregiving appraisals, coping skills of informal caregivers and the condition of people with dementia. Methods: In this randomized controlled and blinded trial, we enrolled 54 informal caregivers of people with dementia visiting the Japan National Center of Geriatrics and Gerontology, and divided them into GMC‐PEI and control groups. The intervention group received a 12‐week GMC‐PEI program that included six 2‐h structured sessions to enhance their knowledge of dementia, caregiving skills and coping skills. The control group received leaflets containing information about dementia. We evaluated caregivers' depression, caregiving time, subjective burden, caregiving appraisal and care coping skills. We also evaluated people with dementia at baseline and 12 weeks, and reassessed 20 participants from the intervention group at 24 and 48 weeks. Results: The GMC‐PEI significantly improved depression, positive appraisals of fulfillment in caregiving, affection for care recipients, self‐growth and coping skills, such as seeking formal support. Depression, fulfillment and affection for people with dementia showed a peak improvement at 24 weeks; formal support‐seeking showed a linear improvement throughout the 48‐week follow‐up period. Conclusions: The group‐based multi‐component psycho‐educational intervention reduced depression, improved self‐appraisal and enhanced coping skills in caregivers. However, emotional enhancements dissipated sooner than support‐seeking skills, suggesting that caregivers should be reviewed every 12–24 weeks. Geriatr Gerontol Int 2021; 21: 561–567 .